RGS10 Reduces Lethal Influenza Infection and Associated Lung Inflammation in Mice - Almutairi, Faris; Sarr, Demba; Tucker, Samantha L.; Fantone, Kayla; Lee, Jae-Kyung; Rada, Balázs (Frontiers in Immunology, 2021)
Seasonal influenza epidemics represent a significant global health threat. The exacerbated immune response triggered by respiratory influenza virus infection causes severe pulmonary damage and contributes to substantial morbidity and mortality. Regulator of G-protein signaling 10 (RGS10) belongs to the RGS proteins family that act as GTPase activating proteins for heterotrimeric G proteins to terminate signaling pathways downstream of G protein-coupled receptors. While RGS10 is highly expressed in immune cells, in particular monocytes and macrophages, where it has strong anti-inflammatory effects, its physiological role in the respiratory immune system has not been explored yet. Here, we show that Rgs10 negatively modulates lung immune and inflammatory responses associated with severe influenza H1N1 virus respiratory infection in a mouse model. In response to influenza A virus challenge, mice lacking RGS10 experience enhanced weight loss and lung viral titers, higher mortality and significantly faster disease onset. Deficiency of Rgs10 upregulates the levels of several proinflammatory cytokines and chemokines and increases myeloid leukocyte accumulation in the infected lung, markedly neutrophils, monocytes, and inflammatory monocytes, which is associated with more pronounced lung damage. Consistent with this, influenza-infected Rgs10-deficent lungs contain more neutrophil extracellular traps and exhibit higher neutrophil elastase activities than wild-type lungs. Overall, these findings propose a novel, in vivo role for RGS10 in the respiratory immune system controlling myeloid leukocyte infiltration, viral clearance and associated clinical symptoms following lethal influenza challenge. RGS10 also holds promise as a new, potential therapeutic target for respiratory infections.